Implementasi Flask Framework pada Development Modul Reporting Aplikasi Sistem Informasi Helpdesk di PT.XYZ) - Santoso, Bartolomeus Bima; Saian, Pratyaksa Ocsa Nugraha (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
PT. XYZ is one of the leading minimarket retail companies in Indonesia. In business, problems often arise that must be resolved. Currently, problem solving is done by using applications built using Oracle Forms. However, the effectiveness and efficiency of the application is considered poor in terms of costs and the reporting process. In this study, the reporting module was developed on an existing application into a website using the Python Flask framework which is open source so that it can increase the effectiveness and efficiency of the module. The research method used is adapted from the Waterfall model stage where at this stage it starts from problem identification to system testing. The result of this research is a website that can be a place for storing information related to company problems. The results of the Black Box Testing test show that the system can function 100%, while the test results with a Likert Scale show 98.1% of potential users agree that the system can function as it should
Keywords: Reporting; Helpdesk Information System; Flask